Locus Coeruleus Neuron Density and Parkinsonism in Older Adults without Parkinson’s Disease - Buchman, Aron S. (2012)
OBJECTIVE: Prior work has showed that nigral neuron density is related to the severity of parkinsonism proximate to death in older persons without a clinical diagnosis of Parkinson’s disease (PD). We tested the hypothesis that neuron density in other brainstem aminergic nuclei is also related to the severity of parkinsonism. DESIGN: We studied brain autopsies from 125 deceased older adults without PD enrolled in the Memory and Aging Project, a clinical-pathologic investigation. Parkinsonism was assessed with a modified version of the Unified Parkinson’s Disease Rating Scale (UPDRS). We measured neuron density in the substantia nigra, ventral tegmental area, locus coeruleus and dorsal raphe; and postmortem indices of Lewy body Alzheimer’s disease and cerebrovascular pathologies. RESULTS: Mean age at death was 88.0 and global parkinsonism was 14.8 (SD=9.50). In a series of regression models which controlled for demographics and neuron density in the substantia nigra, neuron density in the locus coeruleus (Estimate, −0.261, S.E., 0.117, p=0.028) but not in the ventral tegmental area or dorsal raphe was associated with the severity of global parkinsonism proximate to death. These findings were unchanged in models which controlled for post-mortem interval, whole brain weight and other common neuropathologies including Alzheimer’s disease and Lewy body pathology and cerebrovascular vascular pathologies. CONCLUSION: In older adults without a clinical diagnosis of PD, neuron density in locus coeruleus nuclei is associated with the severity of parkinsonism and may contribute to late-life motor impairments.